O direito ao esquecimento na sociedade da (hiper)informação - Rodrigues, Yuri Gonçalves dos Santos (2020)
The society has been changing in a very dinamic way, presenting paradigms every time more complex and, by this way, unreleasead sociocultural situations that need to be glimpsed and faced in the routine, including juridic. Landed in our Supreme Letter, the Federative Republic of Brazil Constitution, the right that give the tittle of this work has been bruised, reflected in the dignity of humam person, that ends in the personality right, the denominated right to be forgotten. In this new juridic horizont presents new guardianship, that has never been thinked years ago as, for exemple, the indentation of the juridic land to the digital harvest. This work aims to study the right to be forgotten in the information society, which, mainly because of the Internet, has brought new challenges to the protection of personality rights against the qualified forms of freedom of speech in all its faces. Based on the classic modes of protection of the right to be forgotten, related to the offender's right to resocialization, it is shown that the claim of being forgotten began to occupy many other areas of civil life and also tha it became an interest of all people included in the information society, associated to various rights of personality. In front this complexity searched by many students and agents Law, raise this work, as a try to undesrstand the way of building the knowledge to show a solid base about the rigth to be forgotten, its origins, concept, peculiarity, aplication and coverage at Brazilian soil and foreign places. . In response to the various complexities found in this way, it was concluded by the feasibility of the right to be forgotten's protection, as long as one considers the elements of the case, that reveal the weights of fundamental rights in collision.